Size differentiation of a continuous stream of particles using acoustic emissions - Nsugbe, Ejay; Starr, Andrew; Foote, Peter; Ruiz Carcel, Cristobal; Jennions, Ian K. (Institute of Physics (IOP), 2016)
Procter and Gamble (P&G) require an online system that can monitor the particle size distribution of their washing powder mixing process. This would enable the process to take a closed loop form which would enable process optimisation to take place in real time. Acoustic Emission (AE) was selected as the sensing method due to its non-invasive nature and primary sensitivity to frequencies which particle events emanate. This work details the results of the first experiment carried out in this research project. This experiment involved the use of AE to distinguish between the sizes of sieved polyethylene particle (53-250microns) and glass beads (150-600microns) which were dispensed on a target plate using a funnel. By conducting a threshold analysis of the impact peaks in the signal, the sizes of the particles could be distinguished and a signal feature was found which could be directly linked to the sizes of the particles.